Primary Sjögren's Syndrome Is Characterized by Distinct Phenotypic and Transcriptional Profiles of IgD+ Unswitched Memory B Cells - Roberts, Mustimbo E. P.; Kaminski, Denise; Jenks, Scott A.; Maguire, Craig; Ching, Kathryn; Burbelo, Peter D.; Iadarola, Michael J.; Rosenberg, Alexander; Coca, Andreea; Anolik, Jennifer; Sanz, Iñaki (Arthritis & rheumatology (Hoboken, N.J.), 2014)
Objective The significance of distinct B cell abnormalities in primary Sjögren's syndrome (SS) remains to be established. We undertook this study to analyze the phenotype and messenger RNA (mRNA) transcript profiles of B cell subsets in patients with primary SS and to compare them with those in sicca syndrome patients and healthy controls. Methods CD19+ B cells from 26 patients with primary SS, 27 sicca syndrome patients, and 22 healthy controls were analyzed by flow cytometry. Gene expression profiles of purified B cell subsets (from 3–5 subjects per group per test) were analyzed using Affymetrix gene arrays. Results Patients with primary SS had lower frequencies of CD27+IgD− switched memory B cells and CD27+IgD+ unswitched memory B cells compared with healthy controls. Unswitched memory B cell frequencies were also lower in sicca syndrome patients and correlated inversely with serologic hyperactivity in both disease states. Further, unswitched memory B cells in primary SS had lower expression of CD1c and CD21. Gene expression analysis of CD27+ memory B cells separated patients with primary SS from healthy controls and identified a subgroup of sicca syndrome patients with a primary SS–like transcript profile. Moreover, unswitched memory B cell gene expression analysis identified 187 genes differentially expressed between patients with primary SS and healthy controls. Conclusion A decrease in unswitched memory B cells with serologic hyperactivity is characteristic of both established primary SS and a subgroup of sicca syndrome, which suggests the value of these B cells both as biomarkers of future disease progression and for understanding disease pathogenesis. Overall, the mRNA transcript analysis of unswitched memory B cells suggests that their activation in primary SS takes place through innate immune pathways in the context of attenuated antigen‐mediated adaptive signaling. Thus, our findings provide important insight into the mechanisms and potential consequences of decreased unswitched memory B cells in primary SS.